Tinjauan: Information Technology Governance Berdasarkan Control Objectives for Information and Related Technology - Maulana, Yoppy Mirza (Jurnal Teknik Informatika dan Sistem Informasi, 2023)
Information technology governance (ITG) is organizational management that aims to ensure the implementation of IT is carried out effectively and efficiently in realizing organizational goals. ITG in ensuring the implementation of IT, through measuring the effectiveness and efficiency of business processes, use of resources, risk management, and improvement of organizational performance. Therefore, ITG has now become the focus of organizational leaders in general and is the core of IT success in organizations. Meanwhile, the success of ITG in an organization is largely determined by the alignment between IT and organizational goals. This alignment can be realized by planning ITG. In making ITG planning, a framework is needed, namely COBIT. Therefore, ITG planning is important for the organization, so that the implementation of IT can be maximized and provide benefits for the organization. On this basis, a narrative review was carried out to explore the ITG planning research based on the COBIT 5 lifecycle. In exploring this research, it is based on formulation planning, implementation, and evaluation. The results of the narrative review which is based on research for the 2018 to 2023 period resulted in a formulation plan but not yet an implementation and evaluation plan. In planning the formulation is only limited to providing recommendations but is not accompanied by an implementation and evaluation plan of the recommendations. For this reason, the results of this narrative review can be used as a basis for further research on ITG planning based on the COBIT 5 lifecycle.